Analyzing the Explanatory Power of Bionic Systems With the Minimal Cognitive Grid - Lieto, Antonio (Frontiers in Robotics and AI, 2022)
In this paper I argue that the artificial components of hybrid bionic systems do not play a direct explanatory role, i.e. in simulative terms, for what concerns their internal mechanisms contributing to determine (in the overall system in which are inserted) a given biological or cognitive function. I ground this analysis on the use of the Minimal Cognitive Grid (MCG), a novel framework proposed in Lieto (2021) to rank the epistemological and explanatory status of artificial systems aiming at modelling (in part or in toto) the behavior of biologically and cognitively inspired artificial systems. Despite the lack of such direct mechanistic explanation of the artificial component, however, I also argue that hybrid bionic systems can have an indirect explanatory role similar to the one played by some AI systems built by using an overall structural design approach (but with the help of partially functional components). In particular, the artificial replacement of part of a biological system can provide i) a local functional account of that part in the context of the overall functioning of the hybrid biological-artificial system ii) global insights about the structural mechanisms of the biological elements connected to such artificial devices.